I presidi antiriciclaggio e il contrasto alla corruzione. L’esperienza dell’Unità di Informazione Finanziaria per l’Italia - Borrello, Italo (Argomenti, 2017)
Corruption and money laundering alter the economy and the competition in financial markets. The fight against these criminal phenomena must be developed not only on the side of the prosecution, but also on the side of the prevention, with administrative tools focused on the detection of suspicious conducts and the protection of the integrity. In the Italian anti-money laundering system the Financial Intelligence Unit acts as a “filter” between the entities obliged to report suspicious transactions and the law-enforcement authorities in charge of financial crimes investigations and prosecutions. The effectiveness of the Italian system has been recognized in the recent mutual evaluation conducted by the FATF-IMF, and the importance of the role of the UIF has been emphasized, due to the quantitative and qualitative growth of STRs, the significant contribution to the detection of financial crimes, and the capacity to cooperate and exchange information at domestic and international level. The fight against corruption could benefit from further consolidation of this role.